SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN KARYAWAN BARU PADA PT. BUDI NABATI PERKASA JAMBI - Sri Mulyati; Lastri Mei Lestari (JURNAL AKADEMIKA)
PT. Budi Nabati Perkasa is a company engaged in the processing industry of CPO into cooking oil with Rose Brand brand and Tawon. In the reception employees, PT. Budi Nabati Perkasa held a reception independently within the PT. Budi Nabati Perkasa. These employees are taken through the recruitment process passes a series of tests conducted. The hardest thing in making a selection factor is the effort to eliminate the subjectivity of a leader or manager so that any choices made are objectively based on the criteria expected by the company. Decision-making in the implementation of a decision support system recruitment using methods SAW (Simple Additive Weighting). The purpose of the final project of this thesis is to create a decision support system that can be used by PT. Budi Nabati Perkasa in the admission process for new employees. Decision support system built using Visual Basic 6.0 and MySQL database relating to research obtained through field studies and literature.